Drymaria cordata: Review on its pharmaconosy, phytochemistry and pharmacological profile - Shivali Singla; Joohee Pradhan; Reena Thakur; Sachin Goyal (Elsevier, 2023)
Absract: Drymaria cordata subsp. diandra (Sw.) J.A. Duke is one of the most important medicinal plants used by various tribes throughout India and the world. It is a traditional herbal medication that is used to treat peptic ulcers, female sterility, headaches, glomerulonephritis, sleeping problems, convulsions, and febrile illnesses in children as an ingredient in many local poly herbal formulations, as well as other major or minor ailments such as cold, headache, coryza, bronchitis, leprosy, tumors, and so on. The plant has been shown to contain a variety of secondary plant metabolites such as alkaloids, flavonoids, tannins, saponins, phenols, and terpenoids which have been proved to show Anti-bacterial, analgesic and anti-pyretic, anti-tussive, anxiolytic, anti-oxidant, anti-diabetic, sinusitis and cytotoxic activities. All the records associated with this plant was accrued from distinctive treatise including reference books, and databases like PubMed, Science Direct, Scopus, Web of Science, Google Scholar, Researchgate, Publons etc. The goal of this paper is to give an outline and critical analysis of the stated traditional uses, anatomy, phytochemistry, pharmacological actions, and toxicology studies of D. cordata, as well as to find the remaining holes and provide a base for further research. The review also tries to get people and academics interested in the wide range of medicinal qualities of the plant so that it can be used better in the future.